Flavor Formation in Chinese Rice Wine (Huangjiu): Impacts of the Flavor-Active Microorganisms, Raw Materials, and Fermentation Technology - Yang, Yijin; Hu, Wuyao; Xia, Yongjun; Mu, Zhiyong; Tao, Leren; Song, Xin; Zhang, Hui; Ni, Bin; Ai, Lianzhong (Frontiers in Microbiology, 2020)
Huangjiu (Chinese rice wine) has been consumed for centuries in Asian countries, and is distinguished for its unique flavor and subtle taste. The flavor compounds of Huangjiu are derived from a wide range of sources, such as raw materials, microbial metabolic activities during fermentation and chemical reactions that occur during aging. Of these sources, microorganisms have the greatest effect on Huangjiu flavour quality. To enrich the microbial diversity, Huangjiu is generally fermented under an open environment, as this increases the complexity of its microbial community and flavor compounds. Thus, understanding the formation of flavor compounds in Huangjiu will be beneficial for producing superior flavored product. In this paper, a critical review of aspects that may affect the formation of Huangjiu flavor compounds is presented. The selection of appropriate raw materials and the improvement of fermentation technology to promote the flavor quality of Huangjiu are discussed. In addition, the effects of microbial community composition, metabolic function of predominant microorganisms and dynamics of microbial community on the flavor quality of Huangjiu are examined. This review thus provides a theoretical basis for manipulating the fermentation process by using selected microorganisms to improve the overall flavor quality of Huangjiu.